Linkage and association of the HLA gene complex with IDDM in 81 Danish families: strong linkage between DR beta 1Lys71+ and IDDM. Issue 11 (November 1996) - Zamani, M; Pociot, F; Spaepen, M; Raeymaekers, P; Nerup, J; Cassiman, J J
Abstract : Many studies have shown an association of IDDM with polymorphisms in the HLA region on chromosome 6p21. Previously our case-control study in the Belgian population showed significant association between IDDM and certain HLA class II alleles, in particular Lys71+, encoding DRB1 alleles. In the present study, 81 Danish multiplex IDDM families and 82 healthy Danish controls were examined for polymorphisms in the HLA-DRB genes and 54 of the 81 families for polymorphisms in HLA-B, -DQA1, -DQB1, -TNFA, and -TNFB genes. The results confirm our previous studies in the Belgian population and show that DRB1Lya71+/+ homozygotes have a relative risk (RR) of 103.5. Linkage between IDDM and DRB1 alleles that encode Lys71+ was shown by affected zib pair analysis which showed strong linkage (p < 1 x 10(-6). By family based association studies, the DRB1Lys71+ was identified as the allale which increased susceptibility to develop IDDM most in the HLA region (haplotype relative risk = 8.38). Haplotype analysis confirmed the increased risk contributed by DRB1Lys71+ alleles and in addition showed that DRB1Lys71- provides protection against IDDM even in the presence of DQB1Aep47-. These results indicate that DRB1Lys71+ screening is a powerful test compared to full HLA typing to determine the risk for a random person to develop IDDM in the Danish population, with an even higher probability than shown previously for the Belgians.